USAGE OF ANKI SPECIALISED PROGRAM APPLICATION DURING FUTURE BORDER GUARD OFFICERS’ INDEPENDENT FOREIGN LANGUAGE PROFESSIONAL TRAINING FOR PASSING STATE EXAMINATION - Ihor H. Bloshchynskyi (Інформаційні технології і засоби навчання, 2017)
Usage of Anki specialised program application during cadets’ independent foreign language professional training at the National Academy of the State Border Guard Service of Ukraine named after Bohdan Khmelnytskyi who study on specialty «State border security and protection» according to the first (bachelor) level of training of higher education for passing state examinations has been revealed in the article. Special attention is given to working out of teaching material (vocabulary decks and cards) for the future border guard officers` training according to the following sections of Anki program: studying of nouns, adjectives, pronouns, verbs, word combinations, expressions for interviewing of foreign citizens, etc.